Pengembangan Sistem Informasi Geografis untuk Produksi Kopi Se-Malang Raya - Febri Fahrizal; Faizatul Amalia; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Malang Raya is the largest coffee producing region in East Java after Banyuwangi and Jember. Besides that, Malang Raya is also an area with a lot of coffee consumption. Many coffee enthusiasts and coffee shops are found. However, many coffee shops supply coffee from distributors who source coffee from outside the Malang area. So that Malang Raya coffee production is not maximized to meet the needs of its own region. Therefore, it is necessary to develop a geographic information system for coffee production in Malang Raya to provide information on coffee production in Malang. In developing the system, the development that is used is waterfall with CodeIgniter and OpenLayers as its framework. The system requirements analysis phase resulted in 4 types of users, 13 functional requirements, and 3 non-functional requirements. The design phase produces sequence diagram modeling, class diagrams, databases, components, and interfaces which are then processed to be implemented at the system implementation phase. The testing phase is done by using white box with a type of base path testing for unit and integration testing, black box for validation testing, a questionnaire with a Likert Scale for availability and consistency testing, and SortSite tools for compatibility testing. So that a system is produced that can display maps and information on coffee production as well as space for farmers to market their products. Based on the test results, it is known that the system is feasible and can be used on various types of browsers.